ANALISIS STRATEGI PENGELOLAAN PIUTANG JATUH TEMPO PADA PT. BINAJASA ABADIKARYA KABIL BATAM - Ita Mustika; Andi Auliya Ramadhany; Akmal Akmal (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
This study aims to determine the strategy or policy of managing receivables due. The object of this research is PT. Binajasa Abadikarya Kabil Batam. This study uses primary data and secondary data. The technique used in collecting data using interview, documentation, and observation techniques. The results of this study can be concluded that the management strategy of overdue receivables is very important, in addition to being a measuring point for the company's success, it can also determine good company performance and maintain company assets for bad debt losses. Receivables management strategy is a policy or action from management where this management strategy is useful for maintaining company assets due to bad debts or bad debts. With the existence of internal control, the company's performance can run well and can obtain accurate financial reports.